2019
DOI: 10.1038/s41598-019-51656-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and In Vitro Functional Analyses of Novel Plant-Produced Anti-Human PD1 Antibody

Abstract: Immunotherapy has emerged as a promising and effective treatment for cancer. The frequently used immunotherapy agents are immune checkpoint inhibitors, such as antibodies specific to PD1, PD-L1, or CTLA-4. However, these drugs are highly expensive, and most people in the world cannot access the treatment. The development of recombinant protein production platforms that are cost-effective, scalable, and safe is needed. Plant platforms are attractive because of their low production cost, speed, scalability, lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(103 citation statements)
references
References 29 publications
8
94
1
Order By: Relevance
“…
Figure 6 Binding of plant-produced mAb CR3022 to RBD protein. The different concentration of plant-produced mAb CR3022, standard human IgG1, and a plant-produced anti-PD1 antibody (as negative control) 28 were incubated on plates coated either with the plant-produced SARS-CoV-2 RBD ( a ) or a commercial CHO-produced RBD ( c ) and detected with an HRP-conjugated anti-human kappa antibody. In parallel, different dilutions of positive convalescent serum collected from a COVID-19 patient and negative serum were also tested for plant-produced RBD ( b ) and CHO-produced RBD binding ( d ).
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…
Figure 6 Binding of plant-produced mAb CR3022 to RBD protein. The different concentration of plant-produced mAb CR3022, standard human IgG1, and a plant-produced anti-PD1 antibody (as negative control) 28 were incubated on plates coated either with the plant-produced SARS-CoV-2 RBD ( a ) or a commercial CHO-produced RBD ( c ) and detected with an HRP-conjugated anti-human kappa antibody. In parallel, different dilutions of positive convalescent serum collected from a COVID-19 patient and negative serum were also tested for plant-produced RBD ( b ) and CHO-produced RBD binding ( d ).
…”
Section: Resultsmentioning
confidence: 99%
“…An immunofluorescence assay was performed to determine whether mAb CR3022 recognize SARS-CoV-2. SARS-CoV-2 was inoculated onto Vero cells and infected cells were incubated with a known positive serum, CR3022, and a negative control antibody 28 before detection with an anti-human IgG conjugated with FITC. The results showed that the plant produced mAb CR3022 could bind to SARS-CoV-2 in infected cells, similar to the positive control serum (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant expression systems have many advantages such as rapid scalability, flexibility, improved safety and high-yield of recombinant proteins at short time [ 29 , 30 ]. Growth factors are extensively studied for their skin renewal activities, wound healing properties, cell growth and collagen biosynthesis.…”
Section: Discussionmentioning
confidence: 99%